The social context of mistreatment: an integrative review - Kawasaki, Shota (2023)
Management scholars have examined various kinds of workplace mistreatment. These investigations and empirical summaries of the literature show that personal experience of mistreatment at work creates a variety of deleterious problems such as more negative job attitudes, lower performance, and poorer health. The bulk of the literature assumes that the key cause-effect relationship resides at the individual level. However, individuals do not experience mistreatment in a vacuum, but rather in a complex social environment that shapes interpretations of, and reactions to, individual mistreatment. In this integrative review, we depart from prior reviews that focus primarily on personal experiences of mistreatment and instead evaluate the literature on mistreatment in the context of others’ negative experiences. Analyzing 64 empirical articles on own and others’ mistreatment at work, we identify six key theoretical perspectives concerning how others’ experiences shape individual reactions to mistreatment. We then develop a sensemaking and social information processing framework for understanding mistreatment in context. We conclude the article by discussing theoretical and methodological recommendations for future research.